The risk of imported malaria in security forces personnel returning from overseas missions in the context of prevention of re-introduction of malaria to Sri Lanka. (December 2016) - Fernando, Sumadhya; Dharmawardana, Priyani; Semege, Saveen; Epasinghe, Geetha; Senanayake, Niroshana; Rodrigo, Chaturaka; Premaratne, Risintha
Abstract Background Sri Lanka is a malaria-free country. However it remains surrounded by countries with endemic malaria transmission. Since the last indigenous case of malaria was reported in October 2012, only imported malaria cases have been diagnosed with 36 cases detected in 2015, which includes 17 cases each ofPlasmodium vivax andPlasmodium falciparum and two cases ofPlasmodium ovale . Methods This study investigated the knowledge and practices regarding malaria chemoprophylaxis among all the Sri Lankan security forces personnel returning from peacekeeping missions in malaria endemic countries over a 7 month period. Adherence to other malaria prevention measures, occurrence of adverse events and incident cases of malaria were also recorded maintaining the anonymity of the respondents. Potential associations for non-compliance were studied. Results Interviews were carried out with 559 security forces personnel returning home from foreign deployments in malaria-endemic regions (males: 550, 98.4 %). The majority (553, 98.9 %) was well aware of the need for chemoprophylaxis during the overseas stay and its regular use as prescribed. The overall adherence to chemoprophylaxis was good with 78.7 % (440/559) reporting regular, as prescribed, use. Having better educational qualifications, being female, being prescribed mefloquine, having fever during deployment and belonging to a security force other than the army were significantly associated with poor compliance (p < 0.05). Conclusions The study reveals that knowledge regarding malaria chemoprophylaxis among Sri Lankan security forces personnel serving abroad was good, a fact that may have contributed to absence/extremely low incidence of malaria during deployment.